Dynamic changes in innate immune responses during direct‐acting antiviral therapy for HCV infection. Issue 3 (3rd January 2019) - Holmes, Jacinta A.; Carlton‐Smith, Charles; Kim, Arthur Y.; Dumas, Emily O.; Brown, Joelle; Gustafson, Jenna L.; Lauer, Georg M.; Silva, Sakuni T.; Robidoux, Maxwell; Kvistad, Daniel; Alatrakchi, Nadia; Tonnerre, Pierre; et al.
Summary: The role of the endogenous interferon (IFN) system has been well characterized during IFN‐based therapy for chronic hepatitis C virus (HCV) infection; less is known for direct‐acting antivirals (DAAs). In this phase 3b open‐label study, we assessed changes in IFN‐stimulated genes (ISGs) in non‐cirrhotic treatment‐naïve or pegIFN/RBV‐experienced HCV‐GT1a‐infected patients receiving paritaprevir/ritonavir/ombitasvir + dasabuvir + ribavirin (PrOD + R) for 12 weeks. ISG expression was quantified from peripheral blood mononuclear cells at baseline, treatment weeks (TW)2, TW4, TW8, end of treatment (EOT) and at post‐treatment week 12. Paired sera were used to assess IFN‐α/IFN‐related chemokines/cytokines. Twenty‐five patients were enrolled. Overall sustained virologic response (SVR)12 was 92% (no virologic failure [VF]) and 100% for those completing the study protocol. Two patients were excluded from the ISG analysis due to lack of post‐treatment samples. The majority of ISGs were downregulated at TW2‐TW4 (nadir TW4); however, a relative increase was observed at TW8‐EOT, although levels were lower than baseline. This downregulation was accompanied by increases in IFN‐α/IFN‐related chemokines, a finding not observed with TH 1/2‐related cytokines. Following SVR, ISG expression returned to TW2 levels. In conclusion, PrOD + R for 12 weeks was well‐tolerated with no VF. Our data demonstrate dynamic alterations in innate immune profiles during highly potent IFN‐free DAA therapy. The downregulation of ISG post‐therapy suggests reversal of the "exhausted" ISG phenotype following SVR, and the rise in ISGs and IFN‐α/IFN‐responsive chemokines late during therapy suggests resetting of IFN responsiveness that may be relevant in determining duration of or immunological sequelae from DAA therapy, including HBV reactivation.